STEAM, inclusion and engagement through makerspaces: the voice of students and teachers - Laura Menichetti; Silvia Micheletta (Je-LKS: Journal of E-Learning and Knowledge Society)
Over the past few decades, there has been a growing interest in tinkering and making, also driven by environmental concerns that define this era. This has led to the rise of creative recycling, facilitated through Do-It-Yourself practices enhanced by digital technologies and practiced in equipped spaces, where commonly used tools and materials are shared by small communities. These makerspaces have also been established in schools, contributing to the adoption of active learning methods, which research shows to be highly effective. The European Erasmus+ “Steam2Go” project aims to create a mobile makerspace that is easily transportable, equipped with pedagogically effective instructions and detailed descriptions of consistent educational experiences. The goal is to make the teaching of STEAM subjects more active, engaging, and inclusive. The pilot experiments conducted with mobile makerspaces involved students (N=184) and teachers (N=15) from various school levels and grades across four partner countries (Cyprus, Greece, Italy, and Poland). The research, conducted through individual questionnaires completed by all participants at the end of the activities, focuses on perceptions and beliefs related to the empowerment achieved by students and teachers. The findings reveal a high level of enjoyment, a perception of improvement in STEAM subjects as well as transversal skills, and a positive appreciation of the Open Educational Resources, which transform the mobile makerspace into an effective educational tool.